2022
DOI: 10.3390/antiox11081598
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antiproliferative and Anti-Enzymatic Capacities, Nutritional Analysis and UHPLC-PDA-MS Characterization of Ungurahui Palm Fruits (Oenocarpus bataua Mart) from the Peruvian Amazon

Abstract: Ungurahui, or Patawa, fruits are a popular fruit and medicinal food used in the Amazon. Here, we have studied nine natural populations of ungurahui from the Peruvian Amazon regarding their nutritional and biological activities, including metal composition, proximal analyses, cytotoxic, antioxidant and cholinesterase inhibition activities. Twenty-four compounds have been detected in these Peruvian natural populations by UHPLC-MS, including nine phenolic acids (peaks 1–6, 8, 9 and 11), four C-glycosyl flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Procedures established by the AOAC were employed in all determinations [ 8 , 9 ]. Moisture content was acquired by drying the fresh fruit samples using an oven at a constant weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures established by the AOAC were employed in all determinations [ 8 , 9 ]. Moisture content was acquired by drying the fresh fruit samples using an oven at a constant weight.…”
Section: Methodsmentioning
confidence: 99%
“…Results are expressed in g per 100 g fresh weight (g/100 g fw). For the mineral content, the spice was dried to ash at 550 °C [ 9 ]. The ash was boiled with 20% hydrochloric acid (10 mL) and then filtered and fit to 100 mL with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the diterpene ent-labda-8,13-E-diene-15-ol isolated from this source was highly cytotoxic (GI 50 , 4.5 ± 0.1 µM), more than the reference drug cisplatin (GI 50 , 4.9 ± 0.2 µM) [4]. Several extracts from Antarctic lichens also showed the good inhibition of those enzymes [5] and some of their isolated phenolic compounds such as usnic acid, barbatolic acid, 5,7-dihydroxy-6-methylphthalide, and atranol, [6], while from native fruits, we can mention the recent study of ungurahui palm datils extracts, which were potent in AChe inhibition (IC 50 2.05 ± 0.03 µg/mL, a sample from the Jenaro Herrera location in Peru) and highly antioxidant (ABTS 1803.72 µmol Trolox/g, for the sample collected in Allpahuayo Mishana, Peru) [7]. In addition, a previous study by some of us demonstrated that samples from Geoffroea decorticans Burkart, fruits from a plant from the Atacama Desert, inhibited α-glucosidase (IC 50 0.8-7.3 µg/mL) and lipase (9.9 to >100 µg/mL) [8].…”
Section: Introductionmentioning
confidence: 94%
“…En cuanto a materia insaponificable, todos los aceites presentaron valores bajos, concordante con lo reportado para aceites extraídos de pulpas de frutos (Quispe et al, 2009). Con respecto al perfil de ácidos grasos, para los cuatro aceites se observa la presencia en forma mayoritaria del ácido oleico (51,40-80,65%), seguido del ácido palmítico (14,77-23,53%), porcentajes similares a los reportados anteriormente para estas especies (Mosquera et al, 2013;Sotero et al, 2013;Vargas-Arana et al, 2022). Cabe destacar el buen contenido de ácido linoleico para O. mapora, con un porcentaje (18,65%), muy superior a lo reportado anteriormente para esta especie (Mosquera et al, 2013).…”
Section: Propiedades Fisicoquímicas Y Composición De áCidos Grasos De...unclassified
“…Existen varios reportes de O. bataua, E. oleracea y E. precatoria, donde son considerados como súper frutas, debido a su alto contenido en aceites, polifenoles y vitaminas, que a su vez les proporcionan una alta actividad antioxidante (Rezaire et al, 2014;Cardona et al, 2013). La pulpa de O. bataua es considerada un alimento altamente nutritivo por su buen contenido de proteína, tocoferoles y aceite saludable, siendo el oleico ω-9 el ácido graso mayoritario (Darnet et al, 2011), presenta buena actividad antioxidante y su consumo puede contribuir a la prevención de enfermedades neurodegenerativas (Vargas-Arana et al, 2022). En el caso de O. mapora, existe poca información reportada sobre los frutos de esta especie, recientemente Muñoz et al (2022) reporta que el aceite del fruto extraído por diferentes métodos, presenta propiedades similares al del aceite de oliva, así como una buena actividad antioxidante que está relacionado con su contenido de fenoles totales.…”
Section: Introductionunclassified